PHYSICAL CHARACTERISTICS OF CULLED MAGELANG DUCK MEAT AFFECTED BY AGING AND MARINATION IN GINGER EXTRACT - Suryanti, U.; Bintoro, V. P.; Atmomarsono, U.; Pramono, Y. B. (Diponegoro University, 2015)
The study was aimed to improve the physical characteristics of culled duck meat using marinationin ginger extract and aging. The material used were Magelang culled ducks (2.5 years old). Gingerextract was derived from the rhizome of fresh ginger (Zingiber officinale Roscoe). The experimentalused was a factorial design (3x3), with two main factors, namely the concentration of ginger extract andaging time in completely randomized design. Level of ginger extract concentrations were 0, 5, 10% andlong times of aging were 24, 48, 72 hours as combination treatments, and replication for each treatmentwere 3 times. There was a significant interaction between the factors of aging time with ginger extractconcentration in influencing moisture, pH , hardness and the water holding capacity of culled Magelangduck meat. The best treatment to improve the physical characteristics of culled duck meat weremarination in 5% ginger extract and aging for 48 hours.